Compound words implementations in “flowers in the attic” novel by VC Andrews - Aprilulloh Yusuf; Shellma Deu Shand (Mitra Palupi, 2021)
Background: Compound word is a word that include of two elements (a root/a word/a phrase and a root/a word) formed a new word and new meaning. Compounding is very important word formation process to know, especially in learning morphology in linguistics where students are required to learn the origin of the word formed. Purpose: The purpose of this study is to find out the types and the meanings of compound words refers to theory of Plag, then to know the types of compound words mostly found in articles. Design and methods: Method of this study used descriptive qualitative research. To collect the data, the writer used documentation technique. From four types of compound, nominal compound is often appearing, because nominal compound is compound words that indicate and refer to the single noun (person, thing, animals, etc.). Results: This result also shows that the compound words not only create new word but also create new meaning. It can use to study about word formation especially in compounding.